Immigration and the Macroeconomy: Some New Empirical Evidence - Francesco Furlanetto; Ørjan Robstad (Norges Bank, 2016)
We propose a new VAR identification scheme that enables us to disentangle immigration shocks from other macroeconomic shocks. Identification is achieved by imposing sign restrictions on Norwegian data over the period 1990Q1 - 2014Q2. The availability of a quarterly series for net immigration is crucial to achieving identification. Notably, immigration is an endogenous variable in the model and can respond to the state of the economy. We find that domestic labor supply shocks and immigration shocks are well identified and are the dominant drivers of immigration dynamics. An exogenous immigration shock lowers unemployment (even among native workers), has a positive effect on prices and on public finances in the medium run, no impact on house prices and household credit, and a negative effect on productivity.
hdl:11250/2495710
Keywords: C11; C32; E32; 330; VAR; labor supply shocks; immigration shocks; job-related immigration; identification